Access Law and Lost Records: A Commentary on "In Search of the Chill" - Forsyth, Ian (Archivaria, 2003)
This commentary reflects on the proposition that records have been lost as a consequence of access to information law. It examines two articles that discuss the effect of legislated access rights on public sector records creators and record-keeping. The commentator applies the factors discussed in both articles to the post-secondary education sector and suggests further ones for consideration. The commentary concludes that no substantial body of evidence exists proving access to information law has had a chill effect on records creation and management but affirms the tactics of resisting access to records does exist. RÉSUMÉ Dans son commentaire, l’auteur tente de réfléchir sur la proposition que la Loi sur l’accès à l’information a entraîné la perte de documents en examinant deux articles qui discutent des effets de la législation des droits d’accès sur les créateurs des documents et sur la gestion des documents dans le domaine public. Il applique les éléments apportés dans les deux articles au secteur de l’éducation post-secondaire et en suggère d’autres pour considération. Il conclut qu’aucune preuve substantielle n’existe pour démontrer que la Loi sur l’accès à l’information a affecté négativement la création de documents et leur gestion. Cependant, les tactiques de résistance à l’accès aux documents existent bel et bien.